Keragaman Berat Lahir Dan Litter Size Ternak Babi Lokal Di Kampung Sabron Sari Distrik Sentani Barat Kabupaten Jayapura Provinsi Papua - Nuhon, Kornelius Liat (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2022)
This study aims to determine the mean, standard deviation, and coefficient of variation in birth weightand number of piglets per birth of local pigs in Sabron Sari Village, West Sentani District, JayapuraRegency. This study used a survey method, namely direct observation to the field to obtaininformation either through a list of questions from five breeders who had sows ready to give birth anddirect weighing of newborn piglets owned by sample farmers that were taken intentionally. From theresults of interviews and direct weighing, it was found that the average birth weight of piglets was 0.74± 0.08 kg, respectively, with a coefficient of variation or diversity of 10.94%; the average number of pigletsper birth was 8.03 ± 1.64 with a coefficient of variation or diversity of 20.39%.